Trends in Emergent Groin Hernia Repair—An Analysis From the Herniamed Registry - Köckerling, Ferdinand; Heine, Till; Adolf, Daniela; Zarras, Konstaninos; Weyhe, Dirk; Lammers, Bernhard; Mayer, Franz; Reinpold, Wolfgang; Jacob, Dietmar (Frontiers in Surgery, 2021)
Introduction While the proportion of emergency groin hernia repairs in developed countries is 2.5%¬–7.7%, the percentage in developing countries can be as high as 76.9%.The mortality rate for emergency groin hernia repair in developed countries is 1.7–7.0% and can rise to 6–25% if bowel resection is needed. In this present analysis of data from the Herniamed Registry, patients with emergency admission and operation within 24 hours are analyzed. Methods Between 2010 and 2019 a total of 13,028 patients with emergency admission and groin hernia repairs within 24 hours were enrolled in the Herniamed Registry. The outcome results were assigned to the year of repair and summarized as curves. The total patient collective is broken down into the subgroups with preoperative manual reduction (taxis) of the hernia content, operative reduction of the hernia content without bowel resection and with bowel resection. The explorative Fisher’s exact test was used for statistical assessment of significant differences with Bonferroni adjustment for multiple testing. Results The proportion of emergency admissions with groin hernia repair within 24 hours was 2.7%. The percentage of women across the years was consistently 33%. The part of femoral hernias was 16%. The proportion of patients with preoperative reduction (taxis) remained unchanged at around 21% and the share needing bowel resection was around 10%. The proportion of TAPP repairs rose from 21.9% in 2013 to 38.0% in 2019 (p<0.001). Between the three groups with preoperative taxis, without bowel resection and with bowel resection, highly significant differences were identified between the patients with regard to the rates of postoperative complications (4% vs 6.5% vs 22.7%; p<0.0001), complication- related reoperations (1.9% vs 3.8% vs 17.7%; p<0.0001) and mortality rate (0.3% vs 0.9% vs 7.5%; p<0.001). In addition to emergency groin hernia repair subgroups female gender and age ≥66 years are unfavorable influencing factors for perioperative outcomes. Conclusion For patients with emergency groin hernia repair the need for surgical reduction or bowel resection, female gender and age ≥66 years have a highly significantly unfavorable influence on the perioperative outcomes.